POTENSI PEMBANGKIT LISTRIK TENAGA AIR HUJAN PLTAH SEBAGAI SUMBER ENERGI LISTRIK PIRANTI ELEKTRONIK RUMAH TANGGA - Anisa, Zuffa; Erwanto , Erwanto (Jurnal Rekayasa Mesin, 2024)
Bibliometric analysis studies of researchers about the use of rainwater as electrical energy are still very few. There is still no utilization of rainwater which is directly used for electrical energy. Analysis of the capacity of the electrical energy requirements of electronic devices shows that the electrical energy requirements for several types of laptops and mobile phones range from (3 – 18) milliwatts per second mWs or (11.02 – 63.13) watt-hour Wh. So that this mini hydropower can be used to turn on LED lights 220 V AC, laptops, and cellphones. Gutters at home that drain water when it rains have a much larger water discharge capacity than a miniature hydropower plant, of course, have enormous potential in independently supplying household electrical energy needs. In which the electrical energy can be used directly or stored in a power saver energy such as Accu, or power bank.